Method for manufacturing OSB (oriented strand board) artificial board
By using sugar and silane to apply the adhesive system separately from isocyanate during the OSB manufacturing process, the pre-hardening problem caused by hardeners is solved, the production speed is improved and the cost is reduced, and more efficient OSB production is achieved.
Patent Information
- Application Number
- CN202380040447.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-18
- Filing Date
- 2023-05-09
- Publication Date
- 2025-01-10
AI Technical Summary
During the manufacturing process of OSB artificial boards, hardeners used in the prior art cause pre-hardening of glue, limiting the production of production equipment and increasing costs, especially when PMDI glue is used, the reaction of hardeners with water leads to polyurethane Deposition affects the efficiency and cost of production equipment.
The adhesive system is applied separately from component A, composed of sugar and silane, and component B, composed of isocyanate, to avoid undesired reactions between the hardener and water, reduce the risk of pre-hardening, and to the sugar-silane reaction product and The combination of isocyanate significantly accelerates the hardening process of the glue and improves the production speed.
The production equipment speed has been improved by at least 10%, the amount of adhesive is reduced, the production cost is reduced, the fossil raw materials used are reduced, the ecological imprint of OSB is improved, and harmful inclusions such as heavy metals and halogen are eliminated.
Smart Images

Figure BDA0005134040560000121 
Figure BDA0005134040560000131 
Figure BDA0005134040560000141
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing an OSB wood-based panel. Background Art
[0002] Coarse-grained board, also known as OSB (Oriented Strand Board), is a man-made board made from long wood chips (wood strands). However, OSB, which originally emerged as a by-product of the veneer and plywood industry, is increasingly being used in timber and prefabricated house construction, because it is light and still meets the static requirements imposed on building panels. OSB is therefore used as building board and wall or roof paneling or also in the flooring sector.
[0003] The production of OSB takes place in a multi-stage process, in which wood chips or shavings are first stripped from debarked logs, preferably needle-shaped wood, in the longitudinal direction by rotating knives. In the subsequent drying process, the natural moisture content of the shavings is reduced at high temperatures. The degree of moisture of the shavings can be varied depending on the adhesive used, wherein the moisture content should be significantly shifted to less than 10% in order to avoid cracks during the subsequent pressing. Depending on the adhesive, it can be more advantageous to wet the shavings rather wet or dry. In addition, during the pressing process, there should be as little moisture as possible in the shavings in order to minimize the steam pressure generated during the pressing process, since otherwise the steam pressure could cause cracks in the raw board.
[0004] After the wood chips have dried, they are introduced into a glue application plant, where glue or adhesive is applied to the wood chips in a finely distributed manner. For the glue application, PMDI (polymeric diphenylmethane diisocyanate) or MUPF glue (melamine-urea-phenol-formaldehyde) is mainly used. The glue can also be applied to OSB in a mixed form. The glue is used because OSB is often used for structural applications, as mentioned above. A moisture-resistant or moisture-proof glue must be used here.
[0005] After the gluing, the gluing chips are spread in a spreading device alternately in the production direction and transversely to the production direction, so that the chips are arranged crosswise in at least three layers (lower cover layer - middle layer - upper cover layer). The spreading direction of the lower cover layer and the upper cover layer is the same here, but it is different from the spreading direction of the middle layer. The chips used in the cover layer and the middle layer are also different from each other. Therefore, the chips used in the cover layer are planar and the chips used in the middle layer are less planar and even sawdust-like. Usually, two material belts are started when manufacturing OSB: one with planar chips for the subsequent cover layer and one with "sawdust" for the middle layer. Correspondingly, the chips in the middle layer can be inferior in quality, because the bending strength is essentially generated by the cover layer. Therefore, fine particles generated during the cutting process can also be used in the middle layer of the OSB board.
[0006] After spreading the wood chips, the wood chips are continuously pressed at high pressure and high temperature, for example, 200°C to 250°C.
[0007] When manufacturing wood-based panels (HWS) such as the described OSB, a non-negligible share of the product costs is caused by the wear and tear of the extremely expensive production equipment. The Contipresses that are currently mostly used here represent a large part of the total cost of the product. In wood-based panels, the hardening of the glue used is always considered to be a limiting factor. In all cases, the glue is hardened by thermal activation. However, since wood is a thermal insulator, the heat transfer from the press to the sawdust cake or fiber cake plays an important role.
[0008] It is known that the hardening of the glue can be accelerated by adding hardeners and thus the system output can be increased. This is a proven method for urea-formaldehyde glues, which are used in large quantities, because hardeners have only a small tendency or no tendency at all to harden the glue at room temperature. This means that little or no pre-hardening occurs during short system downtimes.
[0009] In PMDI glue, this performance is different. Especially the glue used when making OSB has reacted with most hardeners (such as amines, polyols) at room temperature. The hardener also has the following problem usually: the addition to PMDI must be carried out before being applied to the wood chips, including close mixing. Here, the hardener is usually used as an aqueous solution, which causes the additional reaction of PMDI with water to form polyurethane and causes the deposition of polyurethane. The following disadvantages are produced thereby: the output and productivity of the production equipment and the higher costs may be affected less in particular.
[0010] It may be possible to significantly increase production throughput by using chemical formulations that are not traditional hardeners but that still achieve accelerated hardening of the PMDI glue. Summary of the invention
[0011] The technical object on which the invention is based is therefore to increase the productivity of an OSB plant. In this case, if feasible, no technical changes should be necessary. The process should also not increase costs significantly.
[0012] This object is achieved by means of a method for producing OSB having the features of claim 1 .
[0013] Correspondingly, a method for manufacturing an OSB wood-based panel is provided, the method comprising the following steps:
[0014] a) Providing wood shavings;
[0015] b) sizing the wood chips with a binder system comprising:
[0016] - Component A, said component A comprising:
[0017] i) at least one sugar, at least one sugar alcohol or a mixture thereof, and
[0018] ii) at least one compound of formula (I)
[0019] R a 1 SiX (4-a)
[0020] in
[0021] -X is an alkoxy group,
[0022] -R 1 is an organic residue selected from the following: C1-C10 alkyl, the C1-C10 alkyl being capable of being disconnected by -O- or -NH-,
[0023] -R 1 has at least one functional group Q1 selected from the group consisting of a methacrylic group, a methacryloyloxy group, a vinyl group, an alkoxy group, an amino group, an isocyano group and an epoxy group, and
[0024] - a = 0, 1, 2, 3, especially 0, 1 or 2, and
[0025] - a component B consisting of at least one isocyanate,
[0026] wherein component A and component B are applied to the wood chips separately from one another,
[0027] c) spreading the sized wood chips onto a conveyor belt; and
[0028] d) pressing the glued wood particles into OSB panels, and
[0029] Therein, the method is carried out in the production plant at an increase in plant speed of at least 10%, preferably at least 15%, particularly preferably at least 20%, still more preferably at least 25% compared to the initial speed of the production plant.
[0030] In the context of the present invention, in the case of an increase in the plant speed, an acceleration of the plant speed compared to the initial speed of the production plant can be seen. Typically, production plants for OSB production are operated at speeds of up to 340 mm / sec. As can be seen in the embodiments listed below, the present method now allows the process or feed speed to be increased to more than 340 mm / s, preferably more than 380 mm / sec, particularly preferably ≥400 mm / sec. Therefore, the feed speed can be between 400 mm / sec and 460 mm / sec, preferably between 400 mm / sec and 435 mm / sec. It should be noted that the absolute feed speed is related to the length of the production plant and the thickness of the OSB to be produced; i.e. the absolute feed speed can vary from production plant to production plant.
[0031] The use of sugar-containing adhesive compositions in wood-based panels is known. Therefore, EP 3 067 402A1 describes an adhesive composition for wood-based panels, which can be prepared by sugar (for example sorbitol), modified silane (tetraethoxysilane, glycidyloxypropyltriethoxysilane) and isocyanate (PMDI). The adhesive composition is sprayed onto wood shavings as a mixture consisting of the substances, and the wood shavings provided with the adhesive composition are subsequently pressed into OSB. The use of a mixture consisting of three substances prevents PMDI glue from absorbing or diffusing into the wood fibers, which can reduce the amount of adhesive required in the manufacturing method of wood-based panels. The effect is derived as follows: the compound formed by silane compounds and polyols can react with polymer adhesives such as PMDI glue or can also react with the OH groups of wood. The macromolecules produced by the condensation with the glue are no longer able to pass through the hydrophobic fatty acid layer of wood shavings due to the hydrophilic residue. Thus, the current adhesive composition remains on the surface of wood shavings or fibers and does not diffuse into the wood matrix. It can also be said that the polymer binder is now provided with a hydrophilic anchor. According to EP 3 067 402 A1, the use of a mixture of three components, namely sugar, silane, isocyanate, is therefore mandatory before applying the binder to the wood chips in order to achieve a reduction in the amount of binder used.
[0032] EP 3 995 538 A1 describes a sugar-containing binder system for wood-based panels, which consists of three components, namely sugar, polyvinyl alcohol and isocyanate. The three components are applied separately and successively to wood particles for wood-based panels, and the wood particles coated in this way are subsequently pressed into wood-based panels.
[0033] The main difference between this method and the methods described in the prior art is the separate application of component A (sugar and silane) and component B (isocyanate). According to the invention, a 2-component system consisting of component A, which consists of sugar / sugar alcohol and at least one silane, and component B, which consists of isocyanate, is added to the wood chips separately in a mixer (e.g. a tank mixer) or in a sizing drum (coil) during the sizing. Therefore, no mixing of the components of the adhesive system occurs before application to the wood chips, so that, for example, undesired reactions of isocyanate with water from the aqueous solution of component A do not occur. The risk of pre-hardening of the adhesive is thus reduced.
[0034] Furthermore, it has been found that the use of the two-component system according to the invention of sugar-silane reaction product and isocyanate surprisingly results in an acceleration of the production speed. This effect cannot be explained simply.
[0035] As already described in detail above and can be seen from the embodiments described in detail below, the present method now allows the process or feed speed to be increased to more than 340 mm / s, preferably more than 380 mm / sec, particularly preferably ≥ 400 mm / sec. Thus, the feed speed can be 400 mm / sec-460 mm / sec, preferably 400 mm / sec-435 mm / sec.
[0036] According to this, more OSB can be produced with the method according to the invention. The increase in the amount of OSB produced is usually achieved by increasing the amount of glue applied. The increased amount of glue applied is necessary in order to compensate for the lower strength due to the glue that has not yet hardened. It is even more surprising that the demonstrated increase in efficiency is accompanied by a reduction in the amount of glue. The increase in the amount of OSB produced also results in cost advantages with respect to the specific costs of the production plant per cubic meter of OSB produced.
[0037] In addition, as mentioned, the amount of glue is reduced in the method according to the invention, which causes further cost reduction. With a reduction of about 10%, it is possible to achieve several thousand euros in the actual cost for PMDI adhesives at a production volume of up to 2000 cubic meters per day. In addition, this is achieved: the ecological footprint of the manufactured OSB is improved by reducing the use of fossil raw materials for the manufacture of PMDI. A 10% saving corresponds to about 2 kg per cubic meter of OSB, which is 3000 kg per day in the case of 1500 cubic meters of OSB per day, and for PMDI, a saving of up to about 6,000 euros per day has been obtained every day in the case of 2000 euros per ton.
[0038] The silane used in component A is in fact a primer that is intended to improve the adhesion of the isocyanate to the wood chips. Surprisingly, the primer also allows an increase in production speed, which cannot be simply explained because the material classification of the silane is not known for these properties. The 2-component adhesive system is applied either before, together with or after the isocyanate is applied.
[0039] The separate application of the components of the binder system also enables a rapid change in the quantitative ratios of the components of the binder system.Another advantage is that ecologically harmful inclusions such as heavy metals and halogens can be omitted in the binder system.
[0040] In one embodiment, the present method comprises the following steps:
[0041] a) manufacturing wood chips from suitable wood (OSB wood chips),
[0042] b) optionally intermediate storage of the wood chips, in particular in silos or silos,
[0043] c) drying the wood shavings,
[0044] d) Sorting or screening the wood shavings according to their size,
[0045] e) sizing the wood chips with the binder system described in detail above, said binder system comprising component A and component B,
[0046] f) applying the glued wood chips to a conveyor belt by means of air screening and / or throw screening, and
[0047] g) Pressing the sized wood chips arranged on a conveyor belt.
[0048] In addition to the method steps listed above, the wood chips are also freed from foreign matter before they are comminuted, for example during dry or wet cleaning.
[0049] Sugars in Component A
[0050] In one embodiment of component A of the present adhesive system, reducing monosaccharides and / or disaccharides are used. For the purposes of the present application, reducing monosaccharides or disaccharides are understood to be sugars having at least one aldehyde group in a linear state. In contrast, non-reducing sugars do not have free aldehyde groups. An example of a non-reducing disaccharide is sucrose, in which two monosaccharides, namely glucose and fructose, exist in a state of being connected to each other via an α,β-1,2-glycosidic bond in the form of acetal under neutral and alkaline conditions. However, under acidic conditions, sucrose can be cleaved into reducing monosaccharides, namely glucose and fructose.
[0051] In a preferred embodiment, pentoses and hexoses are used as monosaccharides. Pentose and hexoses are selected in particular from the group consisting of: arabinose, ribose, xylose, glucose (dextrose), mannose, galactose and fructose. The sugars mentioned can be used in their D form as well as in their L form.
[0052] In another embodiment, the sugar alcohol is selected from the group consisting of tetravalent alcohols, pentavalent alcohols, and hexavalent alcohols (also called reducing sugars / sugar alcohols). Here, threitol, erythritol, and pentaerythritol are used as tetravalent alcohols, arabitol, adonitol, and xylitol are used as pentavalent alcohols, and sorbitol, mannitol, hexadecene, and dipentaerythritol are used as hexavalent alcohols. The use of sorbitol (or sorbitol) has proven to be particularly advantageous.
[0053] According to this, only polyvalent alcohols based on sugars are used as polyols or polyol compounds. According to this, the use of synthetic polyols such as ethylene glycol, such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol is abandoned. In particular, 1,2-propylene glycol is not currently used as a glue component.
[0054] Silane of component A
[0055] The hydrolyzable residue X of the silane of general formula (I) is advantageously selected from: C 1-6 - alkoxy, especially methoxy, ethoxy, n-propoxy, isopropoxy and butoxy.
[0056] The organic residue R of the silane of the general formula (I) 1 Preferably selected from: C1-C10 alkyl, preferably C1-C8 alkyl, which can be disconnected by -O- or -NH-. Particularly preferred are methyl, ethyl, propyl, pentyl, hexyl, heptyl, octyl.
[0057] In one embodiment of the present composition, at least one functional group Q of the silane of general formula (I) 1 is selected from: epoxy groups, especially glycidyl groups or glycidyloxy groups; methacryloyloxy groups; vinyl groups or isocyanato groups. Particularly preferred functional groups Q 1 is a glycidyloxy group or an isocyanol group. Functional group Q 1 Advantageously, there are residues with double bonds or epoxy groups which can be activated and polymerized by means of UV radiation.
[0058] The functional groups via which crosslinking with the polymeric adhesive and the wood surface is possible include in particular polymerizable and / or polycondensable groups, wherein a polymerization reaction is also understood to be an addition polymerization reaction. The functional groups are preferably selected such that organic crosslinking can be carried out between the polymeric adhesive and the wood surface and optionally also between different adhesive systems via an optionally catalyzed polymerization reaction and / or condensation reaction.
[0059] In a preferred embodiment, the adhesive composition comprises at least two compounds of the general formula (I).
[0060] Thus, in one embodiment, a silane mixture can be used in which the first compound corresponds to the general formula SiX4, wherein X is an alkoxy group, in particular a methoxy group, an ethoxy group, an n-propoxy group or an isopropoxy group, and the second compound corresponds to the general formula R a SiX (4-a) , wherein a=1 or 2, wherein X is an alkoxy group, especially a methoxy, ethoxy, n-propoxy or isopropoxy group, R is a methyl, ethyl, n-propyl or n-butyl group, and Q is a glycidyl group or a glycidyloxy group, an alkoxy group, an amino group or an isocyanato group.
[0061] In another embodiment, a silane mixture can be used in which the first compound corresponds to the general formula SiX4, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, and the second compound corresponds to the general formula R a SiX (4-a) , wherein a=1, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, R is methyl, ethyl, n-propyl or n-butyl, and Q is a glycidyl group or a glycidyloxy group.
[0062] In this case, the molar ratio of the first compound to the second compound can be 0.1 mol to 1 mol, preferably 0.1 mol to 0.5 mol, particularly preferably 0.1 mol to 0.4 mol.
[0063] In a particularly preferred embodiment, tetraethoxysilane, tetramethoxysilane, γ-isocyanatepropyltriethoxysilane, glycidyloxypropyltriethoxysilane, glycidyloxypropyltrimethoxysilane are used as silanes.
[0064] According to one variant, component A comprises a silane mixture in which the first compound corresponds to SiX4, wherein X is an alkoxy group, in particular a methoxy group, an ethoxy group, an n-propoxy group or an isopropoxy group, and the second compound corresponds to the general formula R a SiX (4-a) , wherein a=1 or 2, wherein X is an alkoxy group, especially a methoxy group, an ethoxy group, a n-propoxy group or an isopropoxy group, R is a methyl group, an ethyl group, a n-propyl group or a n-butyl group, and Q is a glycidyl group or a glycidoxy group, an alkoxy group, an amino group or an isocyanato group, and the component A includes a tetravalent alcohol such as threitol, erythritol, pentaerythritol, a pentavalent alcohol such as arabitol, adonitol, xylitol, and a hexavalent alcohol such as sorbitol, mannitol, hexasol, dipentaerythritol.
[0065] According to a preferred variant, component A comprises a silane mixture in which the first compound corresponds to the general formula SiX4, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, and the second compound corresponds to the general formula R a SiX (4-a) , wherein a=1, wherein X is methoxy, ethoxy, n-propoxy or isopropoxy, R is methyl, ethyl, n-propyl or n-butyl, and Q is a glycidyl group or a glycidyloxy group, and the component A includes a hexavalent alcohol such as sorbitol, mannitol, hexadecene, dipentaerythritol.
[0066] According to one particularly preferred variant, component A comprises tetraethoxysilane, glycidyloxypropyltriethoxysilane and sorbitol.
[0067] In another embodiment, it is possible to add component nanoparticles to component A. The particles preferably used here have a size between 2 nm and 400 nm, preferably between 2 nm and 100 nm, particularly preferably between 2 nm and 50 nm. The particles can be especially oxidizing, hydrogen-oxidizing or hydroxyl-oxidizing, which can be produced by various methods, such as ion exchange processes, plasma processes, sol-gel processes, grinding or flame deposition. In a preferred embodiment, particles based on SiO2, Al2O3, ZrO2, TiO2, SnO are used, wherein particularly preferably particles can be used in the form of an aqueous suspension (e.g. with Al 3+ Or Na + Nano-sized SiO2 particles in the form of an acidic suspension of cation-stabilized SiO2.
[0068] In one embodiment, at least one component A consisting of silane and sugar / sugar alcohol is applied to the wood chips, in particular to the wood chips, in an amount of between 0.01% and 0.5% by weight, preferably between 0.02% and 0.4% by weight, particularly preferably between 0.04% and 0.3% by weight, based on absolutely dry wood. Bone dry wood is a unit of measure for the mass of one ton of absolutely dry wood.
[0069] The amount of component A consisting of at least one silane compound of the general formula (I) and at least one sugar / sugar alcohol, based on the amount of isocyanate as component B, can be 0.4 to 20% by weight, preferably 0.8 to 16% by weight, particularly preferably 1.6 to 12% by weight.
[0070] Preferably, at least one component A consisting of silane and sugar / sugar alcohol is used as an aqueous solution with a concentration of 10% to 50% by weight, preferably 12% to 30% by weight, and a corresponding amount of the aqueous solution is used in order to achieve a corresponding final concentration of component A on the wood chips and with respect to the isocyanate.
[0071] The currently used component A of the adhesive composition can be prepared in a process comprising the following steps:
[0072] - providing at least one, preferably at least two different compounds of the general formula (I);
[0073] - the addition of at least one sugar or sugar alcohol;
[0074] - adding at least one catalyst, in particular an acid, to a mixture of at least one compound of the general formula (I) and at least one sugar / sugar alcohol; and
[0075] - Precipitating and separating the reaction mixture from the at least one compound of formula (I) and the at least one sugar / sugar alcohol.
[0076] Inorganic and / or organic acids suitable as catalysts are selected from the group consisting of phosphoric acid, acetic acid, p-toluenesulfonic acid, hydrochloric acid, formic acid or sulfuric acid. Also suitable are ammonium salts, such as ammonium sulfate, which react as weak acids. p-Toluenesulfonic acid is particularly preferred.
[0077] The use of sodium glycerophosphate has proven to be particularly suitable for precipitating the reaction mixture from at least one compound of the general formula (I) and at least one sugar / sugar alcohol. Bases such as NaOH, KOH or ammonium hydroxide solution are also suitable as further precipitants.
[0078] Isocyanate as component B
[0079] In one embodiment, the at least one isocyanate is based on an aromatic polyisocyanate, in particular polydiphenyl diisocyanate (PMDI), toluene diisocyanate (TDI) and / or diphenylmethane diisocyanate (MDI), with PMDI being particularly preferred.
[0080] In one variant, the at least one isocyanate is used in an amount of between 2% and 5% by weight, preferably between 2.2% and 4% by weight, particularly preferably between 2.5% and 3% by weight, based on bone dry wood, in particular sprayed onto the wood chips and / or sawdust.
[0081] The present aqueous binder systems preferably have no further components besides sugars, sugar alcohols and isocyanates. They are therefore free of formaldehyde, synthetic polyols and / or plastics and thickeners, in particular polyvinyl alcohol or polyvinyl acetate or acrylates.
[0082] According to the invention, the binder component is sprayed onto the wood chips as a separate component. Component A can be applied before, during or after the application of the isocyanate as component B.
[0083] As described in detail above, component A is applied to the wood shavings in the form of an aqueous solution. If the isocyanate used as component B now comes into contact with the aqueous solution of component A, the isocyanate readily reacts with water to form polyurethane, wherein the polyurethane formed is deposited in the mixer and clogs the mixer's pipes or spray heads. In order to avoid this, it is therefore advantageous according to the invention to provide the adhesive components separately from one another and to spray them separately from one another onto the wood shavings.
[0084] Mixer / coil
[0085] The application of the adhesive component can be carried out on a size roller (coil) or in a tank mixer.
[0086] The glue application device in web form for the method consists of a cartridge and at least one supply beam for conveying adhesive and compressed air via a spray disk, for driving which a pneumatic drive motor arranged in a housing is provided. Such a glue application device is described in DE 10 2008 046 637 A1.
[0087] Suitable tank mixers are sold, for example, by the company Dieffenbacher. Such glue mixers ensure uniform glue distribution through their large chamber volume and optimal residence time of the material. In order to ensure an optimal glue application result, a constant liquid level in the mixer is maintained by means of a discharge valve.
[0088] After the adhesive component is applied to the wood chips, the sized wood chips are placed or spread on a conveyor belt and then pressed into OSB wood-based panels.
[0089] Pressing can be carried out at a pressing temperature between 150° C. and 250° C., preferably between 180° C. and 220° C., and at a pressing time between 30 sec and 240 sec, preferably between 100 sec and 210 sec, in particular between 150 sec and 180 sec.
[0090] OSB Board
[0091] According to the invention, a rough-strand board, also called OSB (oriented strand board), is produced by the method.
[0092] Thus, the OSB produced by means of the present method has a binder composition comprising:
[0093] at least one component A consisting of at least one silane of the general formula (I) and at least one sugar, at least one sugar alcohol or a mixture thereof;
[0094] - at least one component B comprising at least one isocyanate.
[0095] As detailed above, strand board, also known as OSB (Oriented Strand Board), is produced from long wood chips (wood strands) in a multi-stage process.
[0096] In a first step, wood chips are removed from debarked round wood, preferably needle wood, in the longitudinal direction by means of rotating knives.
[0097] The wood chips produced in this way can have a length of between 50 mm and 200 mm, preferably between 70 mm and 180 mm, particularly preferably between 90 mm and 150 mm; a width of between 5 mm and 50 mm, preferably between 10 mm and 30 mm, particularly preferably between 15 mm and 20 mm; and a thickness of between 0.1 mm and 2 mm, preferably between 0.3 mm and 1.5 mm, particularly preferably between 0.4 mm and 1 mm.
[0098] In one embodiment, the wood chips have, for example, a length of between 150 mm and 200 mm, a width of between 15 mm and 20 mm, a thickness of between 0.5 mm and 1 mm and a moisture content of maximum 50%.
[0099] As mentioned above, OSB is usually composed of two cover layers delimiting a middle layer, wherein the cover layer and the middle layer can be composed of different types of wood shavings. Therefore, planar shavings can be used in the cover layer, while shavings (or sawdust) of poor quality can be used in the middle layer.
[0100] It is also possible to use different types of adhesive systems in the cover layer and the intermediate layer.
[0101] In one embodiment, it can therefore be provided that the wood chips for the top layer(s) and the middle layer of the OSB are each provided with a binder system consisting of component A and component B.
[0102] It is also possible, according to another embodiment, that only the wood chips for the middle layer of the OSB are provided with a binder system consisting of component A and component B, while the wood chips for the cover layer(s) are provided exclusively with isocyanate as binder.
[0103] In both embodiments just described, the amount of isocyanate used in the cover layer is slightly increased relative to the amount of isocyanate used in the intermediate layer.
[0104] The isocyanate is therefore applied to the wood chips for the covering layer in an amount of between 2.5% and 3.5% by weight, preferably between 2.7% and 3.2% by weight, particularly preferably between 2.9% and 3.0% by weight, based on bone dry wood.
[0105] In contrast, the amount of isocyanate applied to the wood chips for the intermediate layer is between 2% and 3% by weight, preferably between 2.2% and 2.8% by weight, particularly preferably between 2.4% and 2.6% by weight, based on bone dry wood.
[0106] The rough particle board (OSB) produced by the described method has a strength of more than 0.3 N / mm 2 , preferably greater than 0.4N / mm 2 , preferably greater than 0.45N / mm 2 , especially preferably greater than 0.5N / mm 2 The transverse tensile strength can be 0.3N / mm 2 and 0.6N / mm 2 In the range between 0.4 N / mm 2 and 0.6N / mm 2 In the range between 0.45 N / mm 2 and 0.55N / mm 2 in the range between.
[0107] Furthermore, the raw strand board (OSB) produced by the described method has a modulus of elasticity in the longitudinal direction of between 3200 MPa and 4000 MPa, preferably between 3400 MPa and 3800 MPa, and a modulus of elasticity in the transverse direction of between 1400 MPa and 1800 MPa, preferably between 1500 MPa and 1600 MPa.
[0108] The OSB artificial board can have a strength of 300kg / m 3 and 1000kg / m 3 Between, preferably 500kg / m 3 and 800kg / m 3 between 600kg / m 3 and 700kg / m 3 The packing density between.
[0109] The thickness of the OSB wood-based panel can be between 5 mm and 50 mm, preferably between 8 mm and 40 mm, with a thickness between 8 mm and 30 mm being particularly preferred. DETAILED DESCRIPTION
[0110] The invention is explained in more detail below with reference to a number of exemplary embodiments.
[0111] Example 1: Preparation of Component A of the Adhesive System
[0112] A mixture of 34.2 g of sorbitol (50% by weight in water) and 4 g of p-toluenesulfonic acid was added with stirring to a mixture of 20.33 g of tetraethylorthosilicate (0.1 mol) and 139.2 g of glycidyloxypropyltriethoxysilane (0.5 mol). In this case, the hydrolysis of the silane mixture and the reaction with sorbitol were carried out, wherein the degree of condensation was intentionally kept low. The course of the reaction and the degree of condensation were followed by Si-NMR measurement.
[0113] After a stirring time of 4 hours, a mixture of 136.8 g of deionized water and 34 g of sodium phosphate was added to the reaction mixture. The mixture was stirred for a further 60 minutes.
[0114] After a standing time of about 1 hour, a two-phase mixture was formed. The lower, now aqueous phase, which contained the reaction product of silane and sorbitol, was separated from the upper alcoholic phase and used as component A.
[0115] Embodiment 2:
[0116] At the OSB line, the covering layer (DS) wood chips in the coil were sprayed with 2.9% by weight PMDI according to the absolute dry wood. In the middle layer (MS), 2.5% by weight PMDI according to the absolute dry wood was added in a trough mixer. Additionally, component A was added in the middle layer (MS) in an amount of 1.6% by weight (0.04% by weight according to the absolute dry wood). Component A was used in a concentration of 12.5% here. The delivery concentration was 50% by weight.
[0117] Before adding component A, a zero sample (sheet thickness: 18 mm) without silane component A is first stretched at a maximum speed of 340 mm / sec, which is usually preset by the quality parameters. After the start of the silane addition, the sample is stretched again. The production speed is then increased to 400 mm / sec or 435 mm / sec. This is the maximum speed at which production can be carried out with the existing amount of sawdust for the intermediate layer. This corresponds to a 27% increase in the machine speed. The sample is stretched at both speeds. Finally, the sample without silane is still stretched at 435 mm / sec. After cooling, some important technical values of the sample are checked.
[0118]
[0119]
[0120] As can be seen from the table, the samples were tested at 0.3 N / mm for OSB3. 2In the transverse tensile strength, the minimum values required according to the standard DIN EN 300, 09 / 2006: Panels made of long, flat, oriented wood chips (OSB) (definitions, classification and requirements) are achieved. In the modulus of elasticity, sample 4 slightly deviates from the required value and sample 5 clearly lies below the required value (3500 MPa and 1400 MPa). In all cases, it can be seen that the values with silane are significantly higher than the control values without silane. The technical values determined for the samples with silane at the maximum speed are also still at the level of sample 1.
[0121] Embodiment 3:
[0122] At the OSB line, the covering layer (DS) wood chips in the coil were sprayed with 2.9 wt % PMDI according to the absolute dry wood. In the middle layer (MS), 2.5 wt % PMDI was added in a trough mixer. The OSB was produced as a zero sample. Then, not only in the covering layer (DS) but also in the middle layer (MS), a silane-containing component A was added.
[0123] In the cover layer (DS), 1.6% by weight of the silane-containing component A was measured with respect to PMDI (0.05% by weight with respect to bone dry wood). In the middle layer (MS), 2.5% by weight of the silane-containing component A was measured with respect to PMDI (0.06% by weight with respect to bone dry wood). Here, the silane was used in a concentration of 12.5%. The delivery concentration was 50% by weight.
[0124] Before the silane addition, a zero sample without silane (sheet thickness: 18 mm) is first stretched at the maximum speed of 340 mm / sec, which is usually preset by the quality parameters. After the start of the silane addition, the sample is stretched again. The production speed is then increased to 400 mm / sec or 460 mm / sec. Due to the lack of wood chips produced for the intermediate layer, the production speed can only be produced for a short time. However, the required sample can be stretched. This corresponds to a 27% increase in the machine speed. The sample is stretched at these two speeds. Finally, at 460 mm / sec, an attempt is still made to stretch the sample without silane. However, gaps will appear at this point. After cooling, some important technical values of the sample are checked.
[0125]
[0126]
[0127] In the tests described, the speed could also be significantly increased. At a feed rate of 460 mm / sec, OSB could no longer be produced without the GS 55.
[0128] The following advantages are obtained:
[0129] - Significant increase in production
[0130] - Reduced risk of pre-hardening
[0131] - Cost reduction.
Claims
1. A method for manufacturing an OSB wood-based panel, the method comprising the following steps: a) Providing wood shavings; b) sizing the wood shavings with a binder system, the binder system comprising: - Component A, said component A comprising: iii) at least one sugar, at least one sugar alcohol or a mixture thereof, and iv) at least one compound of the general formula (I) R a 1 SiX (4-a) in -X is an alkoxy group, -R 1 is an organic residue selected from: a C1-C10 alkyl group, wherein the C1-C10 alkyl group can be disconnected by -O- or -NH-, -R 1 has at least one functional group Q1 selected from the group consisting of a methacrylic group, a methacryloyloxy group, a vinyl group, an alkoxy group, an amino group, an isocyano group and an epoxy group, and - a = 0, 1, 2, 3, especially 0, 1 or 2, and - a component B consisting of at least one isocyanate, wherein the component A and the component B are applied to the wood chips separately from one another, c) spreading the sized wood chips onto a conveyor belt; and d) pressing the glued wood particles into OSB panels, and The method is performed in the production plant at a plant speed which is increased by at least 10%, preferably by at least 15%, particularly preferably by at least 20%, and even more preferably by at least 25% compared to an initial speed of the production plant.
2. The method according to claim 1, characterized in that The at least one sugar of component A is a monosaccharide selected from pentoses and hexoses, in particular selected from: arabinose, ribose, xylose, glucose (dextrose), mannose, galactose and fructose.
3. The method according to any one of claims 1 to 2, characterized in that The at least one sugar alcohol of component A is selected from tetravalent alcohols, pentavalent alcohols and hexavalent alcohols, wherein threitol, erythritol and pentaerythritol are used as tetravalent alcohols, arabitol, adonitol and xylitol are used as pentavalent alcohols, and sorbitol, mannitol, hexadecene and dipentaerythritol are used as hexavalent alcohols.
4. The method according to any one of the preceding claims, characterized in that The residue X of the silane of the general formula (I) is selected from: 1-6 - alkoxy, especially methoxy, ethoxy, n-propoxy, isopropoxy and butoxy.
5. The method according to any one of the preceding claims, characterized in that The organic group R of the silane of the general formula (I) 1 Selected from: C1-C10 alkyl, preferably C1-C8 alkyl, wherein the C1-C10 alkyl can be disconnected by -O- or -NH-.
6. The method according to any one of the preceding claims, characterized in that At least one functional group Q of the silane of the general formula (I) 1 Selected from: epoxy groups, especially glycidyl groups or glycidyloxy groups, methacryloxy groups or isocyanato groups.
7. The method according to any one of the preceding claims, characterized in that At least two silane compounds of the general formula (I) are used.
8. The method according to any one of the preceding claims, characterized in that The at least one component A consisting of silane and sugar / sugar alcohol is applied to the wood chips in an amount of between 0.01% and 0.5% by weight, preferably between 0.02% and 0.1% by weight, particularly preferably between 0.04% and 0.08% by weight, based on bone dry wood.
9. The method according to any one of the preceding claims, characterized in that The at least one isocyanate is polydiphenylmethane diisocyanate (PMDI), toluene diisocyanate (TDI) and / or diphenylmethane diisocyanate (MDI).
10. The method according to any one of the preceding claims, characterized in that The at least one isocyanate is applied to the wood chips in an amount of between 2% and 5% by weight, preferably between 2.2% and 4% by weight, particularly preferably between 2.5% and 3% by weight, based on bone dry wood.
11. The method according to any one of the preceding claims, characterized in that The wood chips used for the cover layer(s) and the middle layer of the OSB are provided with a binder system consisting of component A and component B, respectively.
12. The method according to any one of claims 1 to 10, characterized in that Only the wood chips for the middle layer of the OSB are provided with the binder system composed of component A and component B, whereas the wood chips for the cover layer(s) are provided exclusively with isocyanate as binder.
Citation Information
Patent Citations
Gluing device for strands to manufacture oriented strand board plate, has supply bars feeding glue and compressed-air with spray disks, and spray disks driven by pneumatic drive motors, which are arranged in housing
DE102008046637A1
Binder composition and use of same in wooden boards
EP3067402A1
Sugar-containing binder system for wood material boards, a method for producing a wood material board using this sugar-containing binder system and wood material board obtained by this method
EP3995538A1